2009
DOI: 10.1136/tc.2009.029900
|View full text |Cite
|
Sign up to set email alerts
|

Methods of the International Tobacco Control (ITC) China Survey

Abstract: This paper describes the design features, data collection methods and analytical strategies of the ITC China Survey, a prospective cohort study of 800 adult smokers and 200 adult non-smokers in each of six cities in China . In addition to features and methods which are common to ITC surveys in other countries, the ITC China Survey possesses unique features in frame construction, a large first phase data enumeration and sampling selection; and it uses special techniques and measures in training, field work orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 160 publications
0
52
0
Order By: Relevance
“…Additional detail is provided by Wu et al 15 and in the ITC China Survey Wave 1 Technical Report, which can be found at http://www.itcproject.org 16…”
Section: Methodsmentioning
confidence: 99%
“…Additional detail is provided by Wu et al 15 and in the ITC China Survey Wave 1 Technical Report, which can be found at http://www.itcproject.org 16…”
Section: Methodsmentioning
confidence: 99%
“…The iTC-China survey was conducted through face-toface interviews using a standard protocol. Details of the study methodology have been reported elsewhere (Wu et al, 2010). Briefly, in each city, 10 Jie Dao or Street Districts were selected with probability of selection proportional to population size of the Jie Dao.…”
Section: Samplementioning
confidence: 99%
“…Several items queried potential changes in smoking behavior, including intent to quit smoking in the future (taken from the ITC China survey of the general population conducted in 2006), 12 the Contemplation Ladder (a validated measure of readiness to quit), 13 intent to remain abstinent after hospital discharge, and likelihood of abstinence after hospital discharge. 14 Self-efficacy was assessed by the 12-item version of the Smoking Self-Efficacy Questionnaire (SEQ-12), which has been recently validated among Chinese cardiac patients who smoke.…”
Section: Baseline Measuresmentioning
confidence: 99%
“…15 To facilitate comparisons with the prior ITC survey, self-efficacy was also assessed by the single item used in this survey ("How sure are you that you would succeed in quitting"). 12 Two indices were constructed to measure knowledge of the health risks of smoking. Four items from the ITC China survey assessed knowledge of the general health risks of smoking (Health Risk Index).…”
Section: Baseline Measuresmentioning
confidence: 99%